Participatory Rural Appraisal sebagai Strategi Pemberdayaan Anak di Lembaga Kesejahteraan Sosial Anak di LKSA Pelangi Abepura - Albertina Nasri Lobo; Eddy Pattanduk; Jecqline F Manggaprouw; Tesalonika INT Paron (Assyfa Learning Journal, 2026)
Background: Foster children at the Child Social Welfare Institution (LKSA) Pelangi Abepura often face socioeconomic limitations and lack structured instructional frameworks for professional competency and personal agency development. Objective: This study aims to evaluate the effectiveness of an instructional design using a modified Participatory Rural Appraisal (PRA) strategy to enhance vocational life skills among orphanage children. Method: Employing an experiential and active learning approach, a six-month participatory instructional intervention was conducted with 24 children, integrating structured diagnostic pre-tests, post-tests, focused discussions, and hands-on creative production workshops using local materials. Results: The diagnostic outcomes revealed a significant cognitive and psychomotor transformation; children's conceptual understanding of empowerment jumped from 10% to 90%, and their practical product-design competency increased from 45% to 85%. However, cross-age peer collaboration remains static at 50%, reflecting an age-segregated learning preference. Conclusion: The PRA-driven instructional framework is highly effective in transforming technical expertise into actionable life skills and fostering internal learner motivation, proving itself scalable for institutional non-formal learning ecosystems in remote regions.